Localized States Near a Nonlinear Optical Waveguide - I.V. Gerasimchuk (Журнал нано- та електронної фізики)
In the framework of nonlinear Schrödinger equation the soliton states localized near a nonlinear optical waveguide (defect layer) in optically linear medium are investigated. All the possible localized states in such a system are described.